2018
DOI: 10.1038/s41433-018-0107-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-inverted pedicle internal limiting membrane transposition for large macular holes

Abstract: These findings indicate that the non-inverted pedicle ILM transposition results in a high incidence of anatomic closure with good visual outcome for the treatment of large macular hole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
(27 reference statements)
0
11
0
Order By: Relevance
“… 4 Our previous study reported a new surgical technique of uninverted pedicle ILM transposition for treatment of eyes with large MHs. 5 Our findings indicated that transposition resulted in a high incidence of anatomic closure with good visual outcome for the treatment of large MHs. However, for patients with refractory MHs, vision-related quality of life (QoL) was not just about the closure rate of MHs: it was about visual activity and quality, such as contrast sensitivity.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“… 4 Our previous study reported a new surgical technique of uninverted pedicle ILM transposition for treatment of eyes with large MHs. 5 Our findings indicated that transposition resulted in a high incidence of anatomic closure with good visual outcome for the treatment of large MHs. However, for patients with refractory MHs, vision-related quality of life (QoL) was not just about the closure rate of MHs: it was about visual activity and quality, such as contrast sensitivity.…”
Section: Introductionmentioning
confidence: 52%
“…All the patients received 23 G vitrectomy with ILM peeling combined with autologous ILM transplantation successfully. The surgical method 5 was three channels through pars plana corporis ciliaris being established and the vitreous body being excised. Indocyanine green staining was performed for 15 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…[ 96 97 98 ] A retrospective series of 12 eyes undergoing noninverted pedicle flap for MH >400 μm showed closure rates over 90% with significant improvement in VA and macular sensitivity on mfERG. [ 99 ] However, the pedicle flap has not been widely adopted, and in our experience with its application in refractory holes, the flap tends to retract over time with reopening of the MH.…”
Section: Noninverted Internal Limiting Membrane Flapsmentioning
confidence: 99%
“…To avoid or minimize the damage of retinal microstructure by ILM peeling, some surgeons introduced new techniques aiming to preserve the ILM for IMH [13,14]. Of note, new techniques can only be induced in clinical practice and on condition of not compromising the IMH closure rate.…”
Section: Introductionmentioning
confidence: 99%